Prevalence of gastrointestinal parasitic infections in wild mammals of a safari park and a zoo in Bangladesh - Sabrina Ferdous; Joya Chowdhury; Tanjila Hasan; Pronesh Dutta; Md. Mizanur Rahman; Mohammad Mahmudul Hassan; Md. Rayhan Faruque; Mohammad Abdul Alim (Veterinary Medicine and Science, 2023)
Abstract In safari parks and zoos, wild animals are kept mainly for recreational purposes. Animals in these enclosures are also crucial for the education, research, and conservation aspect. To ensure better management and good health of wild animals in captivity, it is essential to monitor the occurrence of gastrointestinal (GI) parasitic (helminths and protozoa) infections. The current investigation was undertaken to investigate the prevalence of GI parasitic infections in wild mammals at Bangabandhu Sheikh Mujib (BSM) safari park and Chattogram (CTG) zoo of Bangladesh. A total of 72 individual faecal samples were collected from 25 species of wild mammals. Routine qualitative (e.g. direct smear, sedimentation, and flotation) and quantitative (e.g. McMaster technique) tests were performed to identify the eggs or oocysts of helminths and protozoa. Results demonstrated that wild mammals of both BSM safari park and CTG zoo were infected with a total of 17 genera/species of helminths and protozoa. The overall prevalence of GI parasitic infections in wild mammals of both zoological parks was 65.3% (95% confidence interval [CI]: 53.14–76.12), whereas it was 72.4% (95% CI: 52.76–87.27) in the BSM safari park and 60.5% (95% CI: 44.41–75.02) in the CTG zoo. In both zoological parks, infection with nematodes was more frequent compared to other helminth into the wild mammals. The herbivores were more infected with GI parasites than carnivores and omnivores of both BSM safari park and CTG zoo. The mean eggs/oocysts per gram of faeces was the highest in the carnivores compared to herbivores and omnivores of both enclosures. The findings of the current study demonstrated that wild mammals of both BSM safari park and CTG zoo suffered from various GI parasitic infections. Regular monitoring along with proper therapeutic measures may reduce the severe consequences of GI parasitic infections in captive wild animals.